Bihar Third Five-Year Plan Progress Report for the Period Ending December 1963 - Planning Commission (Planning Commission, 1963)
Statement Showing Progress of Plan Expenditure Under The Major Heads Of Development Forthe Quarter Ending 3Jst December, 1963, Agricultural Programme, Co-Operation, C. D. And Grampanchayat, Irrigation And Flood-Control, Power, Industries And Mining, Transport And Communications, Social Services, Miscellaneous